Emancipation through Development Policy? Reflections on Questions of Global Inequality - Bendix, Daniel; Ziai, Aram (Momentum Quarterly, 2015)
Development policy has since long been the object of critique. However, the quality of criticism has reached new heights with Post-Development approaches’ fundamental questioning of development policy as such, which bypasses the common concerns about failures, defects and deficits. Perspectives building on Post-Development also challenge development policy in cases in which it was successful by pointing to inter alia the reproduction of colonial thinking, the disregard of the problematic way of life in the North, the establishment of power relations, the destructive effects of development aid projects and modernisation, and the restriction of a good life to socio-economic indicators. A policy that regards socio-economic inequality to be a problem but that does not wish to ignore Post-Development critique has to address the question of what it might look like on the basis of a reflection and circumvention of the mentioned problematic structures of traditional development cooperation. Such a task is explicated by this paper.
Keywords: development policy; emancipation; post-development; postcolonialism; global inequality